LPS-stimulated microglial cells promote ganglion cell death in organotypic cultures of quail embryo retina - Sierra-Martín, Ana; Navascués, Julio; Neubrand, Veronika E.; Sepúlveda, M. Rosario; Martín-Oliva, David; Cuadros, Miguel A.; Marín-Teva, José L. (Frontiers in Cellular Neuroscience, 2023)
During development microglia colonize the central nervous system (CNS) and play an important role in programmed cell death, not only because of their ability to remove dead cells by phagocytosis, but also because they can promote the death of neuronal and glial cells. To study this process, we used as experimental systems the developing in situ quail embryo retina and organotypic cultures of quail embryo retina explants (QEREs). In both systems, immature microglia show an upregulation of certain inflammatory markers, e.g., inducible NO synthase (iNOS), and nitric oxide (NO) under basal conditions, which can be further enhanced with LPS-treatment. Hence, we investigated in the present study the role of microglia in promoting ganglion cell death during retinal development in QEREs. Results showed that LPS-stimulation of microglia in QEREs increases (i) the percentage of retinal cells with externalized phosphatidylserine, (ii) the frequency of phagocytic contacts between microglial and caspase-3-positive ganglion cells, (iii) cell death in the ganglion cell layer, and (iv) microglial production of reactive oxygen/nitrogen species, such as NO. Furthermore, iNOS inhibition by L-NMMA decreases cell death of ganglion cells and increases the number of ganglion cells in LPS-treated QEREs. These data demonstrate that LPS-stimulated microglia induce ganglion cell death in cultured QEREs by a NO-dependent mechanism. The fact that phagocytic contacts between microglial and caspase-3-positive ganglion cells increase suggests that this cell death might be mediated by microglial engulfment, although a phagocytosis-independent mechanism cannot be excluded.